RETRACTED ARTICLE: Fluorescent labelling in living dental pulp stem cells by graphene oxide quantum dots. Issue 1 (4th December 2019) - Li, Xincong; Guo, Haowei; Ren, Shuangshuang; Fan, Ruirui; Yu, Yijun; Zhang, He; Liu, Chao; Miao, Leiying
Abstract : We, the Editors and Publisher of the journal Artificial Cells, Nanomedicine, and Biotechnology, have retracted the following article: Xincong Li, Haowei Guo, Shuangshuang Ren, Ruirui Fan, Yijun Yu, He Zhang, Chao Liu & Leiying Miao (2019) Fluorescent labelling in living dental pulp stem cells by graphene oxide quantum dots. Artificial Cells, Nanomedicine, and Biotechnology, 47(1), 115–122, DOI: 10.1080/21691401.2018.1544141 Since publication, concerns have been raised about the integrity of the data and the methods presented in the article. When approached for an explanation, the authors have been unresponsive, and we have been unable to verify their original data. We are therefore retracting this article and the corresponding author listed in this publication has been informed. We have been informed in our decision-making by our policy on publishing ethics and integrity and the COPE guidelines on retractions. The retracted article will remain online to maintain the scholarly record, but it will be digitally watermarked on each page as "Retracted".